ANALISIS KONSISTENSI TENAGA KESEHATAN PADA PENERAPAN KESEHATAN DAN KESELAMATAN KERJA DI INSTALASI RAWAT INAP RSUP TADJUDDIN CHALID SELAMA PANDEMI COVID 19 - Andi Khairul Musyawir; Zulfikar A. Sidik; Andi Awaliyah Anwar (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The many risks faced by health workers during COVID-19 are the result of various factors. These include the lack of robust processes to carry out tasks safely, the lack of health logistics supplies, and inadequate protective equipment. These problems not only pose a physical and psychological danger to health workers, but also critically make them transmit the virus (Widiawati et al, 2018). Therefore, it is necessary to consistently implement Occupational Health and Health in hospitals to prevent unintended risks. The purpose of this study is to provide information related to the consistency of health workers in the application of occupational health and safety in the inpatient institution of Tadjuddin Chalid Hospital during the COVID-19 pandemic. The type of research used is qualitative research with direct observation techniques and interviews. The informants in this study were the Head of the Hospital, the Head of the K3 Section.  Head of the inpatient room. And Heads of Training, Doctors, and Nurses. Research from Tajuddin Chalid Hospital Makassar shows that there is no K3 training during this pandemic. Until now, it has only done education through the delivery of messages or templates about the use of PPE. But before the pandemic, we did regular training every year. The conclusion that the maintenance and examination are in accordance with the guidelines of the Minister of Health which says that it is carried out in accordance with real medical needs and applicable medical service standards while still preventing work accidents and wearing PPE